Chiral Triazolium Salts and Ionic Liquids: From the Molecular Design Vectors to Their Physical Properties through Specific Supramolecular Interactions. Issue 3 (29th November 2012) - Porcar, Raul; Ríos‐Lombardía, Nicolás; Busto, Eduardo; Gotor‐Fernández, Vicente; Montejo‐Bernardo, Jose; García‐Granda, Santiago; Luis, Santiago V.; Gotor, Vicente; Alfonso, Ignacio; García‐Verdugo, Eduardo
Abstract An exhaustive experimental study based on X‐ray diffraction analysis, NMR, FTIR‐ATR (attenuated total reflection), and Raman spectroscopy as well as theoretical calculations is reported in order to understand how the non‐covalent intermolecular contacts are fundamental to explain structure–property relationships and allowing us to correlate a basic macroscopic property (i.e., the melting point, Tm) with the structural variables of a family of enantiopure 1, 4‐dialkyl‐1, 2, 4‐triazolium salts. The effect of different structural vectors such as the ring size, the spatial disposition of the substituent, the substitution on the oxygen atom, the nature of the anion, or the N4 alkylation of the triazole on the intermolecular interactions of these chiral salts of a well‐defined 3D structure is reported. The non‐covalent intermolecular contacts mainly implicating the triazolium H3 proton are fundamental to explain structure–property relationships and, therefore, the physical properties of these new chiral salts, rather than simple anion–cation interactions. Overall, our findings highlight the importance of the specific supramolecular interactions for the understanding of the physical properties of triazolium salts and ionic liquids.